2020
DOI: 10.1111/os.12761
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects Comparison and Revision Case Analysis of Unicompartmental Knee Arthroplasty and Open Wedge High Tibial Osteotomy in Treating Medial Knee Osteoarthritis in Patients Under 60 years: A 2–6‐year Follow‐up Study

Abstract: Objective To evaluate the therapeutic effects and revision cases of unicompartmental knee arthroplasty (UKA) and open wedge high tibial osteotomy (OWHTO) in treating medial knee osteoarthritis (MKOA) in patients under 60 years. Methods The present retrospective study included a total of 192 patients who were diagnosed with MKOA and treated by UKA or OWHTO in the Second Affiliated hospital of Xi'an Jiaotong University and Xi'an Honghui Hospital between December 2012 and December 2016. Among these patients, 83 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Among them, there were variation in the selection of outcome indicators and assessment system, and the results were inconsistent. Comparing with previous studies, half of the selected articles were from China (19 from 38 studies) [27][28][29][30][31][32][33][34][35][36] and half of them were updated publications in 2019 and 2020 (19 from 38 studies), [27][28][29][32][33][34][35][36] which were not at all or unfrequently discussed in other systemically quantitative analyses, resulting in obviously different comparison results. In contrast with the meta-analyses by Cao et al 15 Santoso et al 16 and Han et al 17 which observed no significant difference on knee function scores, in this study, higher WOMAC score was found after UKA compared with HTO indicating UKA may produce better functional outcome.…”
Section: Publication Biasmentioning
confidence: 99%
“…Among them, there were variation in the selection of outcome indicators and assessment system, and the results were inconsistent. Comparing with previous studies, half of the selected articles were from China (19 from 38 studies) [27][28][29][30][31][32][33][34][35][36] and half of them were updated publications in 2019 and 2020 (19 from 38 studies), [27][28][29][32][33][34][35][36] which were not at all or unfrequently discussed in other systemically quantitative analyses, resulting in obviously different comparison results. In contrast with the meta-analyses by Cao et al 15 Santoso et al 16 and Han et al 17 which observed no significant difference on knee function scores, in this study, higher WOMAC score was found after UKA compared with HTO indicating UKA may produce better functional outcome.…”
Section: Publication Biasmentioning
confidence: 99%
“…Fourteen studies with 1965 patients reported 176 subjects who underwent revision to TKA. [9,10,14,19,20,25,28,29,31,32,[37][38][39]41] The pooled data showed that the OR for the revision rate was 1.70 (95% CI: 0.74-3.91, I 2 = 73%, P = .21; Fig. 4), and there was no significant difference between the 2 groups.…”
Section: Revision To Tkamentioning
confidence: 99%
“…[13,14,18,19,[21][22][23]26,30,32,33,35,41] Different assessment systems have been used to assess pain. Based on the available data, 7 studies [18,19,21,23,26,35,41] included information on postoperative pain, which was assessed by the visual analogue scale (VAS). [42] The present analysis showed no statistically significant difference between the 2 groups (MD, 0.39, 95% CI: −0.01 to 0.79, I 2 = 91%, P = .06; Fig.…”
Section: Postoperative Painmentioning
confidence: 99%
“…Most patients with knee osteoarthritis(OA) have lesions limited to the medial compartment, and high tibial osteotomy (HTO) and unicompartmental knee arthroplasty (UKA) are well-established treatments for this condition [ 1 3 ]. HTO and UKA, which are often performed as primary surgeries in medial knee OA, report good results as the ultimate treatment for OA with an added advantage of delaying conversion to total knee arthroplasty (TKA) [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, to date, considering which of the two surgical methods to choose remains controversial, comparing long-term survival rates and surgical outcomes [ 6 8 ] In particular, when selecting a surgical method for patients in their 50 s and 60 s, there are many considerations. [ 3 , 9 – 11 ]. Both HTO and UKA have the advantage of saving native joint spaces, but there are some differences in surgical techniques and indications.…”
Section: Introductionmentioning
confidence: 99%